DHX9 helicase promotes R-loop formation in cells with impaired RNA splicing - Prasun Chakraborty (Nature Portfolio, 2018)
Unresolved R-loops can represent a threat to genome stability. Here the authors reveal that DHX9 helicase can promote R-loop formation in the absence of splicing factors SFPQ and SF3B3.